Intracellular Interactions Between Arboviruses and Wolbachia in Aedes aegypti - Reyes, Jerica Isabel L.; Suzuki, Yasutsugu; Carvajal, Thaddeus; Muñoz, Maria Nilda M.; Watanabe, Kozo (Frontiers in Cellular and Infection Microbiology, 2021)
Aedes aegypti is inherently susceptible to arboviruses. The geographical expansion of this vector host species has led to the persistence of Dengue, Zika and Chikungunya human infections. These viruses take advantage of the mosquito’s cell to create an environment conducive for their growth. Arboviral infection triggers transcriptomic and protein dysregulation in Ae. aegypti and in effect, host antiviral mechanisms are compromised. Currently, there are no existing vaccines able to protect human hosts from these infections and thus, vector control strategies such as Wolbachia mass release program is regarded as a viable option. Considerable evidence demonstrates how the presence of Wolbachia interferes with arboviruses by decreasing host cytoskeletal proteins and lipids essential for arboviral infection. Also, Wolbachia strengthens host immunity, cellular regeneration and causes the expression of microRNAs which could potentially be involved in virus inhibition. However, variation in the magnitude of Wolbachia’s pathogen blocking effect that is not due to the endosymbiont’s density has been recently reported. Furthermore, the cellular mechanisms involved in this phenotype differs depending on Wolbachia strain and host species. This prompts the need to explore the cellular interactions between Ae. aegypti-arboviruses-Wolbachia and how different Wolbachia strains overall affect the mosquito’s cell. Understanding what happens at the cellular and molecular level will provide evidence on the sustainability of Wolbachia vector control.